Clinical Utility of Inspiratory Phonation During Laryngeal Stroboscopy for Differential Diagnosis of Vocal Fold Lesions - Hye Rim Chae; Seung Jin Lee; Young Min Park; Hyun Chul Yoon; Jae-Yol Lim (Journal of The Korean Society of Laryngology, Phoniatrics and Logopedics, 2026)
This study aimed to evaluate the utility of inspiratory phonation during laryngeal stroboscopy for diagnosing vocal fold lesions. We compared findings during expiratory and inspiratory phonation in three patients diagnosed with vocal fold paralysis, sulcus vocalis, and squamous cell carcinoma in situ (SCC in situ). During expiratory phonation, supraglottic constriction limited accurate lesion visualization. However, inspiratory phonation demonstrated supraglottic relaxation, revealing clearer lesion boundaries and locations. Specifically, inspiratory phonation enhanced visualization of vocal ligament exposure in sulcus vocalis, bowing in vocal fold paralysis, and tumor margins in SCC in situ. In cases with supraglottic hyperfunction, the true vocal folds were barely visible during expiratory phonation but clearly observed during inspiratory phonation. These findings suggest that inspiratory phonation serves as a valuable diagnostic adjunct in laryngeal stroboscopy, extending beyond its traditional role as a voice therapy technique.